Essentials of Programming in C for Life Sciences - S. Parthasarathy (Ane Books India, 2008)
This book does not assume any prior knowledge of computers or programming and hence, it introduces all the basic concepts starting from the Introduction to Computers and Fundamentals of C along with all the salient features of C namely, Control statements, Functions, Pointers, Structures, Unions, and Data Files in C. The concepts of programming in C are explained keeping in mind the students and research scientists of life sciences. As most of the students of life sciences stream may be less comfortable with mathematical and computational examples, they must be introduced to programming by using simple examples taken from biological sciences. The concepts of programming in C are presented in a simple and easy way to understand through examples taken from both general and Life Sciences, which may kindle interest to learn computer programming to the readers. Written in a self explanatory manner, any student or research scientist of life sciences will be comfortable in learning programming from this book, which will also serve as a very good resource for the teachers